ANALISIS PERUBAHAN HARGA SAHAM DENGAN MENGGUNAKAN GRAFIK CANDLESTICK - Ida Hendarsih (Universitas Bina Sarana Informatika, 2016)
This time the investment has been a staple for most people. There are many reasons that make the investment becomes liberated part of the community. Investment serve as an increase in the value of wealth and investment as a guarantor of future uncertainty. There are several capital market investment products offered by the Indonesia Stock Exchange in Indonesia consists of; stocks, bonds, derivatives, mutual funds, shariah and services around historical data and information IDX Indonesia capital market. In order to menganalisisa value invstasi it must know the tools to analyze price movements on capital markets, one of them using a candlestick chart. Candlestick charts will facilitate assessing the movement of securities. By using a set of technical analysis tools candlestick today the stock market participants can maximize revenue at a level of risk that can be calculated. Many traders consider candlestick charts easier to interpret visually than traditional bar charts. Because candlestick dominant use of colors, it is easy to read the movement of shares and candlestick has four parts (OPEN, HIGH, LOW, CLOSE) in the presence of a body chart. This assessment of the size of the body, long legs or shadow in candlestick. it is easier to see if the stock market goes up or down, how far the rise or decline. In analyzing the stock technically candlestick can be viewed from the perspective of the average price, the lowest price and the highest at a time and price targets. Keyword : Value of Shares, Candlestick Charts